A Method for Modify the Thermal Stress in the Wind Tunnel. (2015) - Ying, Wang; Wei, Wang; Junhui, Bu; Ding, Chen
Abstract: The characteristic of thermal protection structure is very important to the aerocraft. It is necessary to examine the thermal stress of thermal protection structure especially the instantaneous changing of temperature. Thermal protection structure usually has several layers. This paper focused on the thermal stress of inner structure. Unfortunately, instantaneous heating is a very difficult problem especially for the measuring of the thermal stress. This is mainly due to the trouble of modification of these thermal stress data. In this paper, a method of modification for measuring the thermal stress under wind tunnel testing was proposed, and the finite analysis was also used to verify this technique. In order to reduced the modification error, we testing many ways. Firstly, usual calibration was conducted in a usual heating way which means that the temperature grown slowly. We record the data curve of strain gauge and the inner structure during the calibration. Testing was accomplished after calibration. Actual strain data was recorded during the testing; the temperature was also recorded by some thermocouples which located nearby. We modified the actual strain by the calibration data above. After that, we calibrated the affection of velocity of temperature changing to the strain gauge. We used the same material which fabricated the inner structure of thermal protection structure, the same strain gauge, the same scope of temperature and the same of velocity of temperature changing. Many useful results derived from above work. These results were utilized to modify the actual strain. We used finite analysis method to verify the testing results.